ANALISIS KADAR PROTEIN PADA TEPUNG JAGUNG, TEPUNG UBI KAYU DAN TEPUNG LABU KUNING DENGAN METODE KJEDHAL - Nisah, Khairun; Afkar, Majral; Sa'diah, Halimatun (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2019)
Protein is a polymer consisting of amino acid monomers which are connected to form linear bonds called Peptide bonds. The presence of nitrogen is a special feature of protein compounds because this element is not found in simple fat and carbohydrate compounds. This study aims to determine the protein content in corn flour, cassava flour, and pumpkin flour using the Kjedhal method. Protein analysis by the Kjedhal method is basically divided into three stages, namely: the destruction stage, the distillation stage, and the titration stage. The results showed that the protein content in corn flour was 9.32%, cassava flour was 8.45%, and pumpkin flour was 0.62%. The conclusion of this study is the greatest protein content found in corn flour.